1990
DOI: 10.1038/346561a0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a cannabinoid receptor and functional expression of the cloned cDNA

Abstract: Marijuana and many of its constituent cannabinoids influence the central nervous system (CNS) in a complex and dose-dependent manner. Although CNS depression and analgesia are well documented effects of the cannabinoids, the mechanisms responsible for these and other cannabinoid-induced effects are not so far known. The hydrophobic nature of these substances has suggested that cannabinoids resemble anaesthetic agents in their action, that is, they nonspecifically disrupt cellular membranes. Recent evidence, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
2,829
2
90

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,522 publications
(3,001 citation statements)
references
References 18 publications
20
2,829
2
90
Order By: Relevance
“…The psychotropic effects of D-9-THC are mediated by partial agonist effects at CB-1 receptors (CB-1R) where it has modest affinity (K i ¼ 35-80 nmol) and low intrinsic activity (Compton et al, 1992;Gerard et al, 1991;Howlett et al, 2002;Matsuda et al, 1990). However, its hydroxy metabolite has higher affinity and potency.…”
Section: The Mechanism Of the Psychotic Symptoms Induced By D-9-thcmentioning
confidence: 99%
“…The psychotropic effects of D-9-THC are mediated by partial agonist effects at CB-1 receptors (CB-1R) where it has modest affinity (K i ¼ 35-80 nmol) and low intrinsic activity (Compton et al, 1992;Gerard et al, 1991;Howlett et al, 2002;Matsuda et al, 1990). However, its hydroxy metabolite has higher affinity and potency.…”
Section: The Mechanism Of the Psychotic Symptoms Induced By D-9-thcmentioning
confidence: 99%
“…Cannabinoid receptors are a class of cell membrane receptors under the G proteincoupled receptor (GPCR) superfamily (Matsuda et al, 1990). To date, two cannabinoid receptors have been identified by molecular cloning, CB 1 and CB 2 receptors (Howlett et al, 2002;Matsuda et al, 1990;Munro et al, 1993), however the existence of additional CB receptors have also been proposed (Brown, 2007;Pacher et al, 2005;Ryberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To date, two cannabinoid receptors have been identified by molecular cloning, CB 1 and CB 2 receptors (Howlett et al, 2002;Matsuda et al, 1990;Munro et al, 1993), however the existence of additional CB receptors have also been proposed (Brown, 2007;Pacher et al, 2005;Ryberg et al, 2007). Anandamide is a partial or full agonist of CB 1 receptors, depending on the tissue and biological response measured.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study of Swedish conscripts 1,2 and other researches point at a possible causal relationship between schizophrenia and the use of cannabis. 3,[4][5][6] As the discovery of Gprotein-coupled seven-transmembrane-domain cannabinoid receptor (CB1) 7 and the cloning of the brain cannabinoid receptor gene (CNR1), 8 more is known about the mechanisms of action of delta-9-tetra hydrocannabinol, the main active ingredient of cannabis. Binding studies have shown that CB1 receptors are abundantly expressed in the brain, especially in limbic and cortical areas (striatum, substantia nigra, nucleus accumbens).…”
Section: Introductionmentioning
confidence: 99%